Photocatalyst-free visible light driven synthesis of (E)-vinyl sulfones from cinnamic acids and arylazo sulfones. Issue 22 (28th May 2020) - Chawla, Ruchi; Jaiswal, Shefali; Dutta, P.K.; Yadav, Lal Dhar S.
Graphical abstract: Highlights: Photocatalyst-free visible light driven reactions. ( E )-vinyl sulfones from cinnamic acids and arylazo sulfones. Decarboxylative sulfono functionalization protocol. Arylazo sulfones as sulfonyl radical source. Abstract: A photocatalyst-free visible light mediated decarboxylative sulfono functionalization protocol has been explored for the synthesis of ( E )-vinyl sulfones from cinnamic acids and bench-stable arylazo sulfones. The latter have been utilized as sulfonyl radical precursors under blue LED irradiation along with Cs2 CO3, air and KI to obtain the vinyl aryl sulfones as well as vinyl alkyl sulfones in moderate to excellent yields. Besides the non-photocatalytic conditions, high ecosustainability, low cost, ease of operation and access to vinyl alkyl sulfones are certain indispensable traits of the developed method.